DEMONSTRATING THE SYMMETRY AND NON-SYMMETRY COMPONENTS BALANCE IN GRIDS WITH NEUTRAL CONDUCTOR (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2024)
In the context of the ever-increasing complexity of modern power systems, optimizing consumers’ performance to improve electrical energy quality becomes paramount. This article thoroughly examines the power transfer effects in the context of distorting and non-symmetrical regimes in three-phase, four-wire power systems, focusing on heavily nonlinear and unbalanced consumer influence across the grid. Particular emphasis is placed on the impact of these regimes on the parasitic active and reactive powers affecting linear and balanced consumers due to distorting and unbalanced ones. An essential aspect of this analysis is including the neutral conductor in the experimental circuit, enhancing relevance and a more profound understanding of consumer interactions in modern networks. Quantitative aspects of the phenomena involved are assessed from the perspective offered by SCPT (introduced by Andrei Ţugulea), allowing us to identify the source of non-symmetry and residual powers through comprehensive power balance equations for the active and reactive powers.
Keywords: Distribution grid; Active power; Reactive power; Unbalanced consumers; Nonlinear consumers; Țugulea power theory; Powers of symmetry; Powers of non-symmetry; Residual (distorting) powers; Waveforms; Harmonics; Total harmonic distortion (THD)